Composite metal lithium negative electrode, preparation method thereof, lithium secondary battery and device

By adding a lithium buffer layer composed of conductive porous skeleton and lithium-philic material to the surface of the lithium metal negative electrode, uniform deposition of lithium metal and inhibition of lithium dendrites are achieved, and the cycle life and safety hazards caused by lithium dendrites are solved, and the cycle life and safety of lithium secondary batteries are improved.

CN115461891BActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080100246.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-30
Publication Date
2025-04-18
Estimated Expiration
2040-06-30

AI Technical Summary

Technical Problem

The lithium metal negative electrode is prone to form lithium dendrites during the circulation process, resulting in weakening of the battery's circulation performance, which may cause short circuits and fires, posing safety hazards.

Method used

A composite metal lithium negative electrode is adopted, including metal lithium and a lithium buffer layer located on the surface of metal lithium. The lithium buffer layer is composed of a conductive porous skeleton and lithium-philic material. The distribution density of lithium-philic material decreases continuously, inducing lithium metal to deposition from the lithium-philic side to the lithium-philic side, and inhibiting the growth of lithium dendrites.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, improve the cycle life of lithium secondary batteries, and enhance the safety of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115461891B_ABST
    Figure CN115461891B_ABST
Patent Text Reader

Abstract

The present application relates to a composite metal lithium negative electrode, a preparation method thereof, a lithium secondary battery and a device. The composite metal lithium negative electrode provided in the present application comprises metal lithium and a lithium buffer layer located on at least one surface of the metal lithium, wherein the lithium buffer layer comprises a porous skeleton and a lithium-philic material, wherein the porous skeleton is a conductive porous skeleton, and the lithium-philic material is distributed in the porous skeleton; and, in the direction in which the lithium buffer layer is away from the metal lithium, the distribution density of the lithium-philic material in the porous skeleton decreases in a continuous gradient. The present application adds a conductive lithium buffer layer with a lithium-philic property that changes in a continuous gradient on the surface of the lithium metal negative electrode, which can not only provide sufficient migration channels for the deposition and removal of lithium ions, but also induce the uniform deposition of lithium metal in the lithium buffer layer, thereby inhibiting the formation of lithium dendrites and extending the cycle life of the lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a composite metal lithium negative electrode, a preparation method thereof, a lithium secondary battery and a device. Background Art

[0002] Metallic lithium has become the "holy grail" of negative electrode materials for the next generation of high-energy-density secondary batteries due to its high theoretical specific capacity, low reduction potential, minimum atomic radius and low density.

[0003] However, the industrial application of lithium metal anodes is still facing challenges, among which lithium dendrites are a prominent technical problem. In the process of repeated deposition and precipitation of lithium ions, lithium dendrites are inevitably generated. The growth of lithium dendrites not only causes irreversible loss of lithium elements, resulting in weakened battery cycle performance, but also may pierce the diaphragm, causing battery short circuits and even fires, posing a great hidden danger to the use of lithium metal secondary batteries. Therefore, inhibiting the growth of lithium dendrites has become an urgent problem to be solved. Summary of the invention

[0004] In view of the problems existing in the background technology, the present application provides a composite metal lithium negative electrode, a preparation method thereof, a lithium secondary battery and a device.

[0005] In a first aspect, the present application provides a composite metal lithium negative electrode, comprising metal lithium and a lithium buffer layer located on at least one surface of the metal lithium, wherein the lithium buffer layer comprises a porous skeleton and a lithium-philic material, the porous skeleton is a conductive porous skeleton, and the lithium-philic material is selected from one or more of the following substances with lithium-philicity: metal oxides, non-metal oxides, metal sulfides, non-metal sulfides, metal phosphides, non-metal phosphides, metal nitrides or non-metal nitrides. The lithium-philic material is distributed in the porous skeleton, and in the direction in which the lithium buffer layer is away from the metal lithium, the distribution density of the lithium-philic material in the porous skeleton decreases in a continuous gradient.

[0006] In the composite metal lithium negative electrode provided by the present application, in the direction in which the lithium buffer layer is away from the metal lithium, the contact angle of molten lithium in the cross section of the lithium buffer layer increases in a continuous gradient. The size of the contact angle of molten lithium in the cross section of the lithium buffer layer is closely related to the lithium affinity. It indirectly reflects the distribution density of the lithium-affinity material in the porous skeleton. In the direction in which the lithium buffer layer is away from the metal lithium, the contact angle of molten lithium in the cross section of the lithium buffer layer increases in a continuous gradient, indicating that the distribution density of the lithium-affinity material in the porous skeleton decreases in a continuous gradient.

[0007] In the composite metal lithium negative electrode provided in the present application, the lithium buffer layer has an inner surface close to the metal lithium and an outer surface away from the metal lithium, and the contact angle of molten lithium on the inner surface of the lithium buffer layer is 0° to 90°; the contact angle of molten lithium on the outer surface of the lithium buffer layer is 90° to 180°. In the present application, when the contact angles of molten lithium on the inner and outer surfaces of the lithium buffer layer are within the above range, the lithium buffer layer has a better driving force to induce lithium metal to spontaneously deposit from the lithium-phobic side to the lithium-philic side, and has a better effect of inhibiting the growth of lithium dendrites.

[0008] Furthermore, the angle difference Δθ between the contact angle of molten lithium on the outer surface of the lithium buffer layer and the contact angle of molten lithium on the inner surface of the lithium buffer layer is 10° to 180°. Preferably, Δθ is 45° to 135°. When Δθ is within the range defined in the present application, a relatively obvious gradient change in lithium affinity is presented between the inner and outer surfaces, which can effectively drive and induce the deposition of lithium metal from the lithium-phobic side to the lithium-philic side, and effectively improve the deposition utilization rate of the internal space of the porous skeleton of the lithium buffer layer.

[0009] In the composite metal lithium negative electrode provided in the present application, the lithium-philic material is selected from one or more of zinc oxide, zinc sulfide, zinc phosphide, zinc nitride, aluminum oxide, aluminum nitride, magnesium oxide, magnesium sulfide, magnesium nitride, copper phosphide, copper nitride, silver oxide, silver sulfide, and boron nitride; preferably zinc oxide or silver oxide. The above substances all have good lithium affinity and are the preferred choice of lithium-philic materials in the lithium buffer layer of the present application.

[0010] In the composite metal lithium negative electrode provided in the present application, the porous skeleton satisfies at least one of the following conditions (1) to (3): (1) the thickness of the porous skeleton is 1 μm to 10000 μm, preferably 50 μm to 1000 μm; (2) the porosity of the porous skeleton is 30% to 95%; (3) the pore size of the porous skeleton is 0.01 μm to 10 μm. When the thickness of the porous skeleton is within the above range, the lithium buffer layer can have good strength and can provide sufficient internal space for lithium metal deposition, which is beneficial to the improvement of the long cycle performance of the battery. When the porosity of the porous skeleton is 30% to 95%, and / or the pore size of the porous skeleton is 0.01um to 10um, the porous skeleton has a higher specific surface area, which is beneficial to the deposition and release of lithium ions in the skeleton, and also provides sufficient space for the deposition of lithium metal.

[0011] In a second aspect, the present application provides a method for preparing the composite metal lithium negative electrode described in the first aspect, comprising the following steps: dissolving a precursor of a lithium-philic material in a solvent to obtain a lithium-philic material precursor solution; immersing one surface of a porous skeleton substrate in the lithium-philic material precursor solution, taking out and drying, to obtain a porous skeleton substrate loaded with the lithium-philic material precursor; sintering the porous skeleton substrate loaded with the lithium-philic material precursor, and optionally performing a sulfurization treatment, a phosphating treatment or a nitriding treatment to obtain a lithium buffer layer; pressing the lithium buffer layer onto at least one surface of the lithium metal, and bonding the surface immersed in the lithium-philic material precursor solution to the lithium metal, to obtain a composite metal lithium negative electrode.

[0012] In the preparation method of the composite metal lithium negative electrode provided in the present application, the precursor of the lithium-philic material is selected from an organic salt or an inorganic salt containing zinc, aluminum, magnesium, copper, silver or boron. The organic salt is preferably selected from bis(fluorosulfonyl)imide salt and / or bis(trifluoromethylsulfonyl)imide salt; the inorganic salt is preferably selected from one or more of acetate, nitrate, sulfate, thiosulfate or aluminate.

[0013] In the preparation method of the composite metal lithium negative electrode provided in the present application, the solvent used to dissolve the precursor of the lithium-philic material is selected from one or more of water, ethanol, DMF or NMP.

[0014] In the preparation method of the composite metal lithium negative electrode provided in the present application, the porous skeleton substrate satisfies at least one of the following conditions (1) to (3): (1) the thickness of the porous skeleton substrate is 1 μm to 10000 μm, preferably 50 μm to 1000 μm; (2) the porosity of the porous skeleton substrate is 30% to 95%; (3) the pore size of the porous skeleton substrate is 0.01 μm to 10 μm.

[0015] In the preparation method of the composite metal lithium negative electrode provided in the present application, the porous skeleton substrate is selected from one or more of melamine foam, polyurethane, polyethylene, polystyrene, polyvinyl chloride, polypropylene, polyacetylene, polythiophene, polypyrrole, polyaniline, pure carbon, carbon cloth or carbon paper.

[0016] In the preparation method of the composite metal lithium negative electrode provided in the present application, one surface of the porous skeleton substrate is immersed in the lithium-philic material precursor solution for a time of 2 minutes to 360 minutes, preferably 30 minutes to 60 minutes. The range of immersion time provided in the present application helps to ensure that the rate of change of the lithium-philic gradient in the lithium buffer layer is within a suitable range, thereby effectively improving the cycle performance of the lithium secondary battery.

[0017] In the preparation method of the composite metal lithium negative electrode provided in the present application, the sintering treatment is carried out in an inert gas environment. Among them, the sintering time is preferably 0.5 hours to 6 hours, and more preferably 1 hour to 2 hours. The sintering temperature is preferably 400°C to 2500°C, and more preferably 800°C to 1000°C. The above sintering time and sintering temperature conditions can make the porous skeleton achieve better conductivity without over-sintering and consuming the nitrogen element in the porous skeleton.

[0018] In addition, in the preparation method of the composite metal lithium negative electrode provided in the present application, after the sintering treatment, an optional sulfurization treatment, phosphating treatment or nitriding treatment may be performed.

[0019] The sulfurization treatment includes: mixing the lithium buffer layer obtained after the sintering treatment with sulfur powder, and performing sulfurization sintering in an inert gas environment. Preferably, the sulfurization sintering time is 0.5 hours to 6 hours. The sulfurization sintering temperature is 400°C to 1000°C.

[0020] The phosphating treatment includes: mixing the lithium buffer layer obtained after the sintering treatment with phosphorus powder, and performing phosphating sintering in an inert gas environment. Preferably, the phosphating sintering time is 0.5 hours to 6 hours, and the phosphating sintering temperature is 400°C to 1000°C.

[0021] The nitridation treatment includes: nitridation sintering the lithium buffer layer obtained after the sintering treatment in a N2 or NH3 atmosphere. Preferably, the nitridation sintering time is 0.5 hours to 6 hours. The nitridation sintering temperature is 400°C to 1000°C.

[0022] Through the optional sulfidation, phosphation and nitridation steps, the lithium-philic material in the porous framework can be further transformed from metal oxide or non-metal oxide into metal sulfide, non-metal sulfide, metal phosphide, non-metal phosphide, metal nitride or non-metal nitride. The above sulfides, phosphides and nitrides can also play the role of lithium affinity and guide the uniform deposition of lithium metal in the lithium buffer layer of the present invention.

[0023] In a third aspect, the present application provides a lithium secondary battery, which includes the composite metal lithium negative electrode described in the first aspect of the present application.

[0024] In a fourth aspect, the present application provides a device, comprising the lithium secondary battery described in the third aspect of the present application, wherein the lithium secondary battery is used as a power source or energy storage unit of the device.

[0025] Compared with the prior art, this application has at least the following advantages:

[0026] The composite metal lithium negative electrode provided in the present application includes metal lithium and a lithium buffer layer located on at least one surface of the metal lithium. The lithium buffer layer in the present application has two significant characteristics, one is electrical conductivity, and the other is lithium affinity with a continuous gradient change. The applicant believes that: in order to achieve the purpose of suppressing lithium dendrites, if a non-conductive buffer layer is added to the surface of the lithium metal negative electrode, although the actual deposition current density of lithium can be reduced and the formation time of lithium dendrites can be delayed to a certain extent, the non-conductive buffer layer is not conducive to the escape of lithium metal from the buffer layer, which increases the possibility of forming "dead lithium" and is not conducive to the long cycle life of the battery. If a conductive buffer layer is added to the surface of the lithium metal negative electrode, the lithium metal will gain electrons on the outer surface of the buffer layer, which is not conducive to the deposition of lithium metal. The present application adds a conductive buffer layer with a continuous gradient change in lithium affinity on the surface of the lithium metal negative electrode, which can provide sufficient migration channels for the deposition and removal of lithium ions and avoid the formation of "dead lithium" in the lithium buffer layer; it can also induce lithium metal to deposit from the side with less lithium affinity to the side with greater lithium affinity, making full use of the porous space inside the lithium buffer layer, so that lithium metal is uniformly deposited inside the lithium buffer layer, avoiding lithium ions from gaining electrons on the outer surface of the lithium buffer layer, thereby inhibiting the formation of lithium dendrites and extending the cycle life of the lithium metal battery.

[0027] In addition, the present application makes one surface of the porous skeleton substrate immersed in a lithium-philic material precursor solution, so that the distribution density of the lithium-philic material in the porous skeleton decreases in a continuous gradient in the thickness direction of the lithium buffer layer. The preparation method of the composite metal lithium negative electrode of the present application is simple and feasible, with stable technical effects and suitable for industrial applications.

[0028] The lithium secondary battery and the device thereof prepared with the composite metal lithium negative electrode of the present application effectively inhibit the growth of lithium dendrites and have a significantly improved cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a schematic diagram of a contact angle θ of molten lithium in a cross section of a lithium buffer layer in a composite metal lithium negative electrode according to one embodiment of the present application;

[0030] Figure 2 is an electron microscope image of a cross section of a lithium buffer layer in a composite metal lithium negative electrode according to one embodiment of the present application;

[0031] Figure 3 is an electron microscope image of a longitudinal section of a lithium buffer layer in a composite metal lithium negative electrode according to one embodiment of the present application;

[0032] Figure 4 is a three-dimensional diagram of a lithium-ion secondary battery according to a specific embodiment of the present application;

[0033] Figure 5 yes Figure 4An exploded view of a lithium-ion secondary battery is shown;

[0034] Figure 6 is a three-dimensional diagram of a battery module according to a specific embodiment of the present application;

[0035] Figure 7 is a three-dimensional diagram of a battery pack according to a specific embodiment of the present application;

[0036] Figure 8 yes Figure 7 An exploded view of the battery pack shown;

[0037] Fig. 9 is a schematic diagram of a device according to a specific embodiment of the present application;

[0038] Fig.10 This is a comparison chart of the cycle performance of lithium secondary batteries of Example 1 and Comparative Examples 1 to 2 of the present application;

[0039] The reference numerals are described as follows:

[0040] 1 battery pack;

[0041] 2 upper box;

[0042] 3 lower box;

[0043] 4 battery modules;

[0044] 5. Lithium secondary battery;

[0045] 51 housing;

[0046] 52 electrode assembly;

[0047] 53 Top cover assembly. DETAILED DESCRIPTION

[0048] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0049] Composite metal lithium anode

[0050] The first aspect of the present application relates to a composite metal lithium negative electrode, comprising metal lithium and a lithium buffer layer located on at least one surface of the metal lithium, wherein the lithium buffer layer comprises a porous skeleton and a lithium-philic material, wherein the porous skeleton is a conductive porous skeleton; the lithium-philic material is selected from one or more of the following substances having lithium-philicity: metal oxides, non-metal oxides, metal sulfides, non-metal sulfides, metal phosphides, non-metal phosphides, metal nitrides or non-metal nitrides; the lithium-philic material is distributed in the porous skeleton, and in the direction in which the lithium buffer layer is away from the metal lithium, the distribution density of the lithium-philic material in the porous skeleton decreases in a continuous gradient.

[0051] The "lithium affinity" mentioned in this application refers to an affinity for lithium metal. A lithium-affinity material is a material whose contact angle with molten lithium is 0° to 90°. A lithium-phobic material is a material whose contact angle with molten lithium is 90° to 180°. Specifically, the lithium affinity of a material can be tested by the following method: a powdered material is pressed under a certain pressure to form a sheet material, and after drying, molten lithium metal is dropped onto a cross-section of a lithium buffer layer, and a special measuring instrument for measuring the surface contact angle (such as the commercially available contact angle meter of the German Krues Company) is used for measurement. Among them, the contact angle is defined as: the angle between the solid-liquid interface and the tangent of the liquid-gas interface at the junction of the solid, liquid and gas phases.

[0052] The surface of the lithium metal negative electrode in the present application has a lithium buffer layer with a conductivity whose lithium affinity presents a continuous gradient change. The lithium buffer layer can provide sufficient migration channels for the deposition and removal of lithium ions and avoid the formation of "dead lithium" in the lithium buffer layer; it can also induce lithium metal to spontaneously deposit in the buffer layer from the side with less lithium affinity to the side with greater lithium affinity, making full use of the porous space inside the lithium buffer layer to achieve uniform deposition of lithium metal, avoiding lithium ions from gaining electrons on the outer surface of the lithium buffer layer, thereby inhibiting the formation of lithium dendrites and extending the cycle life of the lithium metal battery.

[0053] In the embodiment of the present application, in the direction in which the lithium buffer layer is away from the metallic lithium, the contact angle of molten lithium in the cross section of the lithium buffer layer increases continuously in a gradient. The cross section of the lithium buffer layer refers to: the contact surface between the lithium buffer layer and the metallic lithium is the first surface, and the cross section of the lithium buffer layer parallel to the first surface is the cross section of the lithium buffer layer.

[0054] In the present application, the cross section of the lithium buffer layer can be obtained by various testing methods known in the art, such as laser ion cutting or blade cutting.

[0055] The contact angle of molten lithium in the cross section of the lithium buffer layer can be measured as follows: molten lithium metal is dropped onto a cross section of the lithium buffer layer, and a special measuring instrument for measuring the surface contact angle (such as the contact angle meter of the German Krues Company on the market) is used for measurement. Wherein, the contact angle is defined as: the angle between the solid-liquid interface and the tangent of the liquid-gas interface at the intersection of the solid, liquid and gas phases. The contact angle of molten lithium in the cross section of the lithium buffer layer reflects the wettability of molten lithium metal on the cross section of the lithium buffer layer, that is, the ability of molten lithium metal to spread or gather on the cross section of the lithium buffer layer. The contact angle of molten lithium in the cross section of the lithium buffer layer is also a manifestation of the lithium affinity of the cross section. The smaller the contact angle of molten lithium in a cross section of the lithium buffer layer, the better the wettability of molten lithium metal in the cross section, and the better the lithium affinity of the cross section; the larger the contact angle of molten lithium in a cross section of the lithium buffer layer, the worse the wettability of molten lithium metal in the cross section, that is, the weaker the lithium affinity of the cross section. Figure 1 This is a schematic diagram of the molten lithium contact angle θ of the cross section of the lithium buffer layer in the composite metal lithium negative electrode according to one embodiment of the present application, wherein 1-A shows the case where θ is less than 90° and 1-B shows the case where θ is greater than 90°.

[0056] In the embodiment of the present application, the surface of the lithium buffer layer close to the metal lithium is defined as the inner surface, and the surface of the lithium buffer layer away from the metal lithium is defined as the outer surface, and the contact angle of molten lithium on the inner surface or outer surface of the lithium buffer layer is measured. Similarly, the contact angle of molten lithium on the inner surface or outer surface of the lithium buffer layer can be measured as follows: molten lithium metal is dropped onto the inner surface or outer surface of the lithium buffer layer, and a special measuring instrument for measuring the surface contact angle is used (for example, a commercially available contact angle meter from Kruess, Germany) for measurement.

[0057] In some embodiments of the present application, the contact angle of molten lithium on the inner surface of the lithium buffer layer is 0° to 90°. The contact angle of molten lithium on the outer surface of the lithium buffer layer is 90° to 180°. At this time, the wettability of lithium metal in a molten state on the inner surface of the lithium buffer layer is good, and the inner surface of the lithium buffer layer is a lithiophilic surface; the wettability of lithium metal in a molten state on the outer surface of the lithium buffer layer is poor, and the outer surface of the lithium buffer layer is a lithiophobic surface. When the lithium buffer layer has a lithiophilic inner surface and a lithiophobic outer surface, the lithium buffer layer has a better driving force to induce lithium metal to spontaneously deposit from the lithiophobic side to the lithiophilic side, and the effect of inhibiting the growth of lithium dendrites is better.

[0058] In some embodiments of the present application, the angle difference Δθ between the contact angle of molten lithium on the outer surface of the lithium buffer layer and the contact angle of molten lithium on the inner surface of the lithium buffer layer is 10° to 180°. Preferably, Δθ is 45° to 135°. Δθ shows the rate of change of the lithium affinity gradient between the inner and outer surfaces of the lithium buffer layer. The rate of change of the lithium affinity gradient affects the driving force of the lithium buffer layer to induce the deposition of metallic lithium in its skeleton. When Δθ is within the range defined in the present application, a relatively obvious lithium affinity gradient change is presented between the inner and outer surfaces, which can effectively drive and induce the deposition of lithium metal from the lithium-phobic side to the lithium-philic side, and effectively improve the deposition utilization rate of the internal space of the porous skeleton of the lithium buffer layer.

[0059] In some embodiments of the present application, the lithium-philic material is selected from one or more of zinc oxide, zinc sulfide, zinc phosphide, zinc nitride, aluminum oxide, aluminum nitride, magnesium oxide, magnesium sulfide, magnesium nitride, copper phosphide, copper nitride, silver oxide, silver sulfide, and boron nitride. Preferably, the lithium-philic material is zinc oxide or silver oxide. All of the above substances have good lithium affinity and are preferred choices for the lithium-philic materials in the lithium buffer layer of the present application.

[0060] In some embodiments of the present application, the porous skeleton satisfies at least one of the following conditions (1) to (3): (1) the thickness of the porous skeleton is 1 μm to 10000 μm, preferably 50 μm to 1000 μm; (2) the porosity of the porous skeleton is 30% to 95%; (3) the pore size of the porous skeleton is 0.01 μm to 10 μm.

[0061] When the thickness of the porous skeleton is in the range of 1 μm to 10000 μm, preferably in the range of 50 μm to 1000 μm, the lithium buffer layer can have good strength and can provide sufficient internal space for lithium metal deposition, which is beneficial to improving the long cycle performance of the battery.

[0062] When the porosity of the porous skeleton is 30% to 95%, and / or the pore size of the porous skeleton is 0.01um to 10um, the porous skeleton has a high specific surface area, which is conducive to the deposition and release of lithium ions in the skeleton, and also provides sufficient space for the deposition of lithium metal. Among them, the porosity of the porous skeleton refers to the ratio of the total volume of the tiny voids in the porous skeleton to the total volume of the porous skeleton. The pore size of the porous skeleton refers to the diameter of the pores in the porous skeleton.

[0063] In the present application, the thickness of the porous skeleton has a well-known meaning in the art and can be measured by using well-known instruments and methods in the art, for example, using a cross-sectional SEM method to test the thickness of 10 regional samples and taking the average value.

[0064] In the present application, the porosity of the porous skeleton is a well-known meaning in the art and can be measured by instruments and methods well-known in the art, for example, using the AccuPyc II 1340 fully automatic true density tester of Micromeritics, USA, and referring to the national standard GB / T 24586-2009 for testing.

[0065] In the present application, the pore size of the porous skeleton can be measured using instruments and methods known in the art. Exemplary test methods can refer to the standards GB / T19587-2017 "Determination of Specific Surface Area of ​​Solid Materials by Gas Adsorption BET Method" and GB / T21650.2-2008 Mercury Intrusion and Gas Adsorption Method for Determination of Pore Size Distribution and Porosity of Solid Materials - Part 2: Analysis of Mesopores and Macropores by Gas Adsorption Method. For example, the pore size of the porous skeleton can be tested using the American Micromeritics TriStar II 3020 instrument.

[0066] Figure 2 This is an electron microscope image of a cross section of a lithium buffer layer in a composite metal lithium negative electrode according to an embodiment of the present application. Among them, 2-A shows the morphology of the porous skeleton inside the lithium buffer layer. 2-B shows the distribution of C, N, Zn, and O elements in a cross section of the lithium buffer layer. It can be seen that the two elements Zn and O are densely distributed in the lithium buffer layer. 2-C is an enlarged view of 1-A. It can be seen that there is no obvious precipitation of large ZnO particles on the porous skeleton, indicating that ZnO is evenly distributed in the porous skeleton in the form of small particles.

[0067] Figure 3 It is an electron microscope image of a longitudinal section of a lithium buffer layer according to an embodiment of the present application. Among them, 3-A shows the morphology of a longitudinal section of the lithium buffer layer. It can be seen that the gradient distribution of the lithium-philic material in the porous skeleton has no effect on the overall structure of the porous skeleton. 3-B shows the distribution of Zn elements in a longitudinal section of the lithium buffer layer, wherein the surface with a larger Zn element distribution density is the inner surface of the lithium buffer layer, and the surface with a smaller Zn element distribution density is the outer surface of the lithium buffer layer; it can be seen that the distribution density of the Zn element in the porous skeleton changes in a continuous gradient.

[0068] Preparation of composite lithium metal anode

[0069] In some embodiments of the present application, a method for preparing a composite lithium metal negative electrode is provided, comprising the following steps: dissolving a precursor of a lithium-philic material in a solvent to obtain a lithium-philic material precursor solution; immersing one surface of a porous skeleton substrate in the lithium-philic material precursor solution, taking out and drying, to obtain a porous skeleton substrate loaded with the lithium-philic material precursor; sintering the porous skeleton substrate loaded with the lithium-philic material precursor, and optionally performing a sulfurization treatment, a phosphation treatment or a nitridation treatment to obtain a lithium buffer layer; pressing the lithium buffer layer onto at least one surface of the lithium metal, and making the surface of the porous skeleton substrate immersed in the lithium-philic material precursor solution adhere to the lithium metal, to obtain a composite lithium metal negative electrode.

[0070] In some embodiments of the present application, the precursor of the lithium-philic material is selected from an organic salt or an inorganic salt containing zinc, aluminum, magnesium, copper, silver or boron. Preferably, the organic salt is selected from a bis(fluorosulfonyl)imide salt (such as ZnFSI) and / or a bis(trifluoromethylsulfonyl)imide salt (such as ZnTFSI, AgTFSI). The inorganic salt is selected from one or more of acetate, nitrate, sulfate, thiosulfate or aluminate.

[0071] In some embodiments of the present application, the solvent used to dissolve the precursor of the lithium-philic material is selected from one or more of water, ethanol, DMF or NMP.

[0072] In some embodiments of the present application, the porous skeleton substrate is selected from one or more of melamine foam, polyurethane, polyethylene, polystyrene, polyvinyl chloride, polypropylene, polyacetylene, polythiophene, polypyrrole, polyaniline, pure carbon, carbon cloth or carbon paper. Among them, polyacetylene, polythiophene, polypyrrole, polyaniline, pure carbon, carbon cloth or carbon paper itself has conductivity. Melamine foam, polyurethane, polyethylene, polystyrene, polyvinyl chloride, polypropylene itself does not have conductivity, and can obtain conductivity after high-temperature sintering. The above-mentioned porous skeleton substrates can all be used to prepare the composite metal lithium negative electrode of the present application. The conductive porous skeleton in the composite metal lithium negative electrode can provide sufficient migration channels for the deposition and removal of lithium ions, promote the induction effect of the lithium buffer layer on the lithium metal deposition, and improve the cycle life of the battery.

[0073] In some embodiments of the present application, a surface of the porous skeleton substrate is immersed in a lithium-philic material precursor solution for a period of 2 minutes to 360 minutes. Preferably, the immersion time is 30 minutes to 60 minutes. The immersion time affects the diffusion of the lithium-philic material precursor solution inside the porous skeleton matrix. The range of immersion time provided in the present application helps to ensure that the rate of change of the lithium-philic gradient in the lithium buffer layer is within a suitable range, thereby effectively improving the cycle performance of the lithium secondary battery.

[0074] In some embodiments of the present application, the sintering process is carried out in an inert gas environment. The sintering time is preferably 0.5 hours to 6 hours. More preferably, the sintering time is 1 hour to 2 hours. The sintering temperature is preferably 400°C to 2500°C. More preferably, the sintering time is 800°C to 1000°C. The above sintering time and sintering temperature conditions can make the porous skeleton achieve better conductivity without over-sintering and consuming nitrogen in the porous skeleton.

[0075] In some embodiments of the present application, after the porous skeleton substrate loaded with the lithium-philic material precursor is sintered, an optional sulfurization treatment, phosphating treatment or nitriding treatment may be performed.

[0076] The sulfurization treatment performed in some embodiments of the present application includes: mixing the lithium buffer layer obtained after the sintering treatment with sulfur powder, and performing sulfurization sintering in an inert gas environment. Preferably, the sulfurization sintering time is 0.5 hours to 6 hours. The sulfurization sintering temperature is 400°C to 1000°C.

[0077] The phosphating treatment performed in some embodiments of the present application includes: mixing the lithium buffer layer obtained after the sintering treatment with phosphorus powder, and performing phosphating sintering in an inert gas environment. Preferably, the phosphating sintering time is 0.5 hours to 6 hours. The phosphating sintering temperature is 400°C to 1000°C.

[0078] The nitridation treatment performed in some embodiments of the present application includes: nitridation sintering the lithium buffer layer obtained after the sintering treatment in a N2 or NH3 atmosphere. Preferably, the nitridation sintering time is 0.5 hours to 6 hours. The nitridation sintering temperature is 400°C to 1000°C.

[0079] Through the optional sulfidation, phosphidation and nitridation steps, the lithium-philic material in the porous framework can be further transformed from metal oxide or non-metal oxide into metal sulfide, non-metal sulfide, metal phosphide, non-metal phosphide, metal nitride or non-metal nitride. The above sulfides, phosphides and nitrides can also play the role of lithium affinity and guide the uniform deposition of lithium metal in the lithium buffer layer of the present invention.

[0080] Lithium secondary battery

[0081] The third aspect of the present application provides a lithium secondary battery, which includes the composite metal lithium negative electrode described in the first aspect of the present application.

[0082] In some embodiments of the present application, a lithium secondary battery may include a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the negative electrode sheet is the composite metal lithium negative electrode described in the first aspect of the present application.

[0083] The method for preparing the lithium secondary battery should be known to those skilled in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet can each be a layer body, so that they can be cut into a target size and stacked in sequence, and can also be wound to a target size to form a battery cell, and can be further combined with an electrolyte to form an electrochemical energy storage device.

[0084] In a lithium secondary battery, a positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. In the positive electrode sheet, the positive electrode active material layer can be disposed on one surface of the positive electrode current collector or on both surfaces of the positive electrode current collector.

[0085] Those skilled in the art may select a suitable method to prepare the positive electrode sheet, for example, the method may include the following steps: mixing the positive electrode active material, the binder, and the conductive agent to form a slurry, and then coating the slurry on the positive electrode current collector.

[0086] Among them, there is no particular restriction on the specific type of positive electrode active material, as long as it can meet the requirements of embedding and extracting lithium ions. The positive electrode active material can be a layered structure material that allows lithium ions to diffuse in a two-dimensional space, or a spinel structure that allows lithium ions to diffuse in a three-dimensional space. Preferably, the positive electrode active material can be selected from one or more of lithium transition metal oxides, lithium transition metal oxides, and compounds obtained by adding other transition metals or non-transition metals or non-metals. Specifically, the positive electrode active material can be preferably selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphates containing olivine structure.

[0087] The general formula of the lithium-containing phosphate with an olivine structure may be LiFe1-x-yMnxM'yPO4, 0≤x≤1, 0≤y<1, 0≤x+y≤1, M' is selected from one or more of other transition metal elements or non-transition metal elements except Fe and Mn, and M' is preferably selected from one or more of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr. Preferably, the lithium-containing phosphate with an olivine structure is selected from one or more of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.

[0088] The lithium transition metal oxide is selected from one or more of LiCoO2, LiMnO2, LiNiO2, LiMn2O4, LiNixCoyMn1-x-yO2, LiNixCoyAl1-x-yO2, and LiNixMn2-xO4, wherein 0<x<1, 0<y<1, and 0<x+y<1. Preferably, the lithium transition metal oxide is selected from one or more of LiCoO2, LiNi1 / 3Co1 / 3Mn1 / 3O2, LiNi0.5Co0.2Mn0.3O2, LiNi0.6Co0.2Mn0.2O2, LiNi0.8Co0.1Mn0.1O2, LiNi0.8Co0.15Mn0.05O2, LiNi0.8Co0.15Al0.05O2, LiNi0.5Mn1.5O4, and LiMn2O4.

[0089] In the positive electrode sheet, the positive electrode active material layer may also include a conductive agent and a binder, wherein the types and contents of the conductive agent and the binder are not specifically limited and can be selected according to actual needs. The binder generally includes a fluorinated polyolefin binder. Relative to the fluorinated polyolefin binder, water is generally a good solvent, that is, the fluorinated polyolefin binder generally has good solubility in water. For example, the fluorinated polyolefin binder may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives. In the positive electrode material layer, the mass percentage content of the binder may be due to the poor conductivity of the binder itself, so the amount of the binder cannot be too high. Preferably, the mass percentage content of the binder in the positive electrode active material layer is less than or equal to 2wt% to obtain a lower electrode sheet impedance. The conductive agent of the positive electrode plate can be any conductive agent suitable for lithium-ion (secondary) batteries in the art, for example, it can be a combination of one or more of acetylene black, conductive carbon black, carbon fiber (VGCF), carbon nanotube (CNT), Ketjen black, etc. The weight of the conductive agent can account for 1wt% to 10wt% of the total mass of the positive electrode material layer. More preferably, the weight ratio of the conductive agent to the positive electrode active material in the positive electrode plate is greater than or equal to 1.5:95.5.

[0090] In the positive electrode sheet, the type of positive electrode current collector is not specifically limited and can be selected according to actual needs. The positive electrode current collector can usually be a layer body, and the positive electrode current collector is usually a structure or part that can collect current. The positive electrode current collector can be various materials in the art that are suitable for use as a positive electrode current collector for an electrochemical energy storage device. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to nickel foil and aluminum foil.

[0091] In lithium secondary batteries, the separator can be any material suitable for use in separators of electrochemical energy storage devices in the art, for example, a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0092] In lithium secondary batteries, the electrolyte can be any electrolyte suitable for electrochemical energy storage devices in the art. For example, the electrolyte generally includes an electrolyte and a solvent, and the electrolyte generally includes a lithium salt. More specifically, the lithium salt can be an inorganic lithium salt and / or an organic lithium salt, and specifically can include but is not limited to a combination of one or more of LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiN(CF3SO2)2 (abbreviated as LiTFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), and LiBF2C2O4 (abbreviated as LiDFOB). For another example, the concentration of the electrolyte can be 0.8 mol / L to 1.5 mol / L. The solvent may be any solvent suitable for use in an electrolyte of an electrochemical energy storage device in the art. The solvent of the electrolyte is generally a non-aqueous solvent, preferably an organic solvent, and specifically may include but is not limited to ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, or a combination of one or more of their halogenated derivatives.

[0093] Figure 4 shows a perspective view of a lithium-ion secondary battery according to a specific embodiment of the present invention, Figure 5 yes Figure 4 An exploded view of a lithium-ion secondary battery is shown. Figure 4 and Figure 5 According to the present application, the lithium-ion secondary battery 5 (hereinafter referred to as the battery cell 5) includes an outer package 51, an electrode assembly 52, a top cover assembly 53 and an electrolyte (not shown). The electrode assembly 52 is accommodated in the housing 51, and the number of the electrode assembly 52 is not limited, and can be one or more.

[0094] It should be noted that Figure 4 The battery cell 5 shown is a can-type battery, but the present application is not limited thereto. The battery cell 5 may be a pouch-type battery, that is, the housing 51 is replaced by a metal plastic film and the top cover assembly 53 is eliminated.

[0095] In some embodiments, lithium-ion secondary batteries may be assembled into a battery module. The battery module may contain a plurality of lithium-ion secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 6 4 is a perspective view of a battery module 4 as an example. Figure 6In the battery module 4, the plurality of lithium-ion secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. The plurality of lithium-ion secondary batteries 5 may further be fixed by fasteners. Optionally, the battery module 4 may further include a housing having a storage space, and the plurality of lithium-ion secondary batteries 5 are stored in the storage space.

[0096] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack. Figure 7 is a stereoscopic view of a battery pack 1 as an example, Figure 8 yes Figure 7 Exploded view of the battery pack shown. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0097] Device

[0098] The fourth aspect of the present application provides a device, which includes the lithium secondary battery of the third aspect of the present application, and the lithium secondary battery is used as a power source of the device or an energy storage unit of the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0099] The device can select a lithium secondary battery, a battery module or a battery pack according to its usage requirements.

[0100] Fig. 9 A schematic diagram of a device according to a specific embodiment of the present application is shown. The device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the device's requirements for high power and high energy density of a lithium-ion secondary battery (i.e., the secondary battery of the present application), a battery pack or a battery module may be used.

[0101] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a lithium-ion secondary battery (ie, the secondary battery of the present application) may be used as a power source.

[0102] The advantages of the present application are further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application. Unless otherwise specified, the various parameters involved in this specification have general meanings known in the art and can be measured by methods known in the art. For example, it is possible to test according to the method provided in the examples of the present application. In addition, the preferred ranges and options of the various different parameters provided in the various preferred embodiments can be combined arbitrarily, and the various combinations obtained therefrom are all considered to be within the scope of the disclosure of the present application.

[0103] (I) The influence of the materials and preparation process of the lithium buffer layer on the technical effect of the present application

[0104] Examples 1 to 38

[0105] Preparation of composite lithium metal anode

[0106] The precursor of the lithium-philic material is dissolved in a solvent to obtain a lithium-philic material precursor solution; one surface of the porous skeleton substrate is immersed in the lithium-philic material precursor solution for several hours; the porous skeleton substrate after immersion is taken out from the lithium-philic material precursor solution, placed in an oven, and dried at 80°C for 12 hours; then placed in a tubular furnace, sintered in an inert atmosphere to obtain a lithium buffer layer; the lithium buffer layer is pressed on at least one surface of the metallic lithium, and the surface of the porous skeleton substrate immersed in the lithium-philic material precursor solution is bonded to the metallic lithium to obtain a composite metallic lithium negative electrode.

[0107] The positive electrode sheet, separator and electrolyte are prepared according to conventional methods in the art.

[0108] Positive electrode sheet: LiNi0.8Co0.1Mn0.1O2, conductive carbon and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 96:2:2 to prepare a positive electrode slurry for a lithium-ion battery with a certain viscosity. The positive electrode slurry is coated on a current collector aluminum foil, dried at 85°C and then cold pressed, and then trimmed, cut and slit. After slitting, the slurry is dried at 85°C for 4 hours under vacuum conditions, and the tabs are welded to make a positive electrode sheet for a lithium battery.

[0109] Isolation membrane: The porous substrate diaphragm material is a polyethylene microporous film with a thickness of 16um.

[0110] Electrolyte: Dissolve lithium hexafluorophosphate in a mixed solvent consisting of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1 to obtain the desired electrolyte.

[0111] Preparation of lithium secondary batteries

[0112] The positive electrode sheet, the composite metal lithium negative electrode, and the separator between the positive electrode sheet and the negative electrode sheet are wound and assembled, and the electrolyte is injected to make a lithium-ion battery. The lithium-ion is a soft-pack battery with an electrode active area of ​​40cm2 and a battery design capacity of 140mAh.

[0113] Comparative Example 1

[0114] Different from the embodiment, lithium metal is directly used as the negative electrode, and a ternary positive electrode is matched without a buffer layer to assemble a lithium metal battery.

[0115] Comparative Example 2

[0116] Different from the embodiment, a 200 μm thick melamine foam is directly sintered at 800° C. for 2 h and pressed onto the surface of lithium metal to serve as a negative electrode; it is then matched with a ternary positive electrode to be assembled into a lithium metal battery.

[0117] Comparative Example 3

[0118] Different from the embodiment, two sheets of 100 μm thick melamine foam are respectively immersed in a mixed solution of ethanol and water containing 0.1M and 1M zinc acetate, and maintained for 720 min to ensure that zinc acetate is fully and evenly diffused into the melamine foam, and there is no concentration gradient in the monolayer. The soaked melamine foam is placed in an oven, dried overnight at 80°C, and then placed in a tubular furnace, sintered in an inert atmosphere at 800°C for 2h, and then taken out and pressed on the lithium metal surface in sequence, with the carbon layer with a high zinc acetate concentration facing the lithium metal side, that is, a lithium metal protective layer is also added on the lithium metal surface, and the protective layer also has a lithium affinity gradient, but this lithium affinity gradient is discontinuous. The above-mentioned composite metal lithium negative electrode is matched with a ternary positive electrode to assemble a lithium metal battery.

[0119] The specific parameters of Examples 1 to 38 and Comparative Examples 1 to 3 are shown in Table 1.

[0120] Cycle performance test:

[0121] The specific test method is: at 25°C, constant current charging and constant current discharging are used, the charging and discharging voltage range is 2.8~4.3V, the charging and discharging rate is 0.2C, the initial capacity of the battery is recorded as C0, and the battery completes a full charge and discharge, which is recorded as a cycle; charge and discharge according to the above method, and test the battery capacity after each cycle until the battery capacity is 80%*C0, and record the number of cycles at this time.

[0122] The battery cycle performance test results of Examples 1 to 38 and Comparative Examples 1 to 3 are shown in Table 2.

[0123] Table 1

[0124]

[0125]

[0126] Table 2

[0127]

[0128]

[0129] Analysis of battery cycle performance test results:

[0130] (1) Examples 1 to 13, Comparative Examples 1 to 3

[0131] Examples 1 to 13 show the effect of adding the lithium buffer layer of the present application on the surface of the metal lithium negative electrode of the lithium secondary battery on the battery cycle performance of the lithium secondary battery. As can be seen from Table 1, Examples 1 to 5 respectively selected different lithium-philic material precursors to prepare lithium-philic material precursor solutions; Examples 1, 6 to 9 respectively selected different solvents to prepare lithium-philic material precursor solutions; and Examples 1, 10 to 13 respectively selected different porous skeleton substrates.

[0132] It can be seen from Table 2 that the lithium secondary batteries of Examples 1 to 13 are charged and discharged under 0.2C conditions, and the number of cycles until the capacity decays to 80% is more than 190, and even exceeds 200. In contrast, the lithium secondary battery of Comparative Example 1, which uses only metallic lithium as the negative electrode, is charged and discharged under the same conditions, and the number of cycles until the capacity decays to 80% is only 41; and Comparative Example 2, which only uses a porous skeleton substrate pressed on the surface of metallic lithium to form a negative electrode sheet, is charged and discharged under the same conditions, and the number of cycles until the capacity decays to 80% is only 134. The above comparative data show that in the embodiments of the present application, the lithium buffer layer prepared using different types of lithium-philic materials and different types of porous skeletons can induce lithium metal to form a uniform deposition in the lithium buffer layer, avoid lithium ions from gaining electrons on the surface of the lithium buffer layer, and thus improve the cycle performance of the lithium secondary battery.

[0133] Fig.10 The cycle performance of the lithium secondary batteries of Example 1 and Comparative Examples 1 to 2 is shown. Fig.10 It can be seen that the cycle performance attenuation of Example 1 is significantly better than that of Comparative Examples 1 and 2.

[0134] In addition, Comparative Example 3 forms a buffer layer with a discontinuous lithium-philic gradient on the surface of the lithium metal negative electrode. In Comparative Example 3, the buffer layer added to the surface of the metal lithium negative electrode is composed of two porous skeleton layers with different distribution densities of lithium-philic materials. During the battery cycle, lithium metal will inevitably undergo uneven deposition in the porous skeleton layers with the same distribution density of lithium-philic materials. It can be seen from Table 2 that under the same conditions, the number of cycles for the capacity of the lithium secondary battery of Comparative Example 3 to decay to 80% is only 145, which is significantly lower than Example 1 of the present application; it can be seen that the inhibitory effect of Comparative Example 3 on lithium dendrites and the improvement of the battery cycle life are weaker than those of the present application.

[0135] (2) Examples 1, 14 to 19

[0136] Examples 1 and 14 to 19 show the influence of the immersion time of one surface of the porous skeleton substrate in the lithium-philic material precursor solution on the technical effect of the present application.

[0137] As can be seen from Table 1, Examples 1, 14 to 19 all use 200 μm thick melamine foam as a porous skeleton matrix, and immerse one surface thereof in a mixed solution of ethanol and water containing 1M zinc acetate; only the immersion time is different, which is 1h, 1min, 2min, 30min, 120min, 360min, and 720min. Other materials and preparation process parameters are the same. As can be seen from Table 2, with the extension of the immersion time, the cycle performance of the lithium secondary battery shows a trend of first rising and then falling.

[0138] When the immersion time is too short (such as Example 14), the lithium-philic material precursor solution does not have enough time to diffuse into the porous skeleton matrix, and is insufficient to inhibit the growth of lithium dendrites in the lithium metal negative electrode, resulting in the cycle performance of the lithium secondary battery being only slightly improved compared to Example 2 where a lithium buffer layer is not added.

[0139] As the immersion time increases, the precursor solution of the lithium-philic material diffuses into the porous skeleton substrate through one surface of the porous skeleton substrate, and gradually forms a continuous gradient concentration distribution in the porous skeleton substrate, which also forms a continuously decreasing lithium-philicity in the lithium buffer layer in the composite metal lithium negative electrode. The lithium buffer layer's inhibition and induction of deposition of lithium dendrites in the metal lithium negative electrode gradually become obvious, and its improvement of the cycle performance of lithium secondary batteries also becomes significant.

[0140] However, the longer the immersion time of the porous skeleton substrate in the lithium-philic material precursor solution is not necessarily better. In Example 1, the immersion time of the porous skeleton substrate in the lithium-philic material precursor solution is 1 hour, and the lithium secondary battery has a very good cycle performance. If the immersion time is further extended, the lithium-philic material precursor solution can continue to diffuse and penetrate into the porous skeleton substrate, which will cause the lithium-philic gradient in the porous skeleton to gradually disappear, and the improvement effect on the cycle performance of the lithium secondary battery will also weaken. As in Example 19, since the immersion time of the porous skeleton substrate in the lithium-philic material precursor solution is as long as 720 minutes, the improvement effect on the cycle performance of the lithium secondary battery is not as good as in Example 1.

[0141] Therefore, in the embodiment of the present application, the time for immersing one surface of the porous skeleton substrate in the lithium-philic material precursor solution is preferably 2 minutes to 360 minutes, and more preferably 30 minutes to 60 minutes.

[0142] (3) Examples 1, 20 to 25

[0143] Examples 1, 20 to 25 show the influence of the temperature conditions of sintering a porous skeleton substrate loaded with a lithium-philic material precursor in an inert atmosphere on the technical effect of the present application.

[0144] As can be seen from Table 1, in Examples 1, 20 to 25, the sintering temperatures of the porous skeleton substrate loaded with the lithium-philic material precursor solution in an inert atmosphere are 800°C, 200°C, 400°C, 1000°C, 1500°C, 2000°C and 2500°C, respectively, and other materials and preparation process parameters are consistent. As can be seen from Table 2, with the increase of the sintering temperature, the cycle performance of the lithium secondary battery shows a trend of first rising and then falling.

[0145] When the sintering temperature is low (such as Example 20), the porous skeleton of the lithium buffer layer does not achieve optimal conductivity, which is not conducive to the migration and release of lithium metal from the buffer layer, resulting in limited improvement in the cycle performance of the lithium secondary battery.

[0146] As the sintering temperature increases, the conductivity of the lithium buffer layer is gradually improved. The lithium buffer layer's inhibition and induction of deposition of lithium dendrites at the metal lithium negative electrode gradually becomes more obvious, and the improvement of the cycle performance of the lithium secondary battery is also enhanced. In Example 1, the porous skeleton substrate loaded with a lithium-philic material precursor solution is sintered at a temperature of 800°C in an inert atmosphere, which significantly improves the cycle performance of the lithium secondary battery.

[0147] However, a sintering temperature that is too high not only wastes energy, but also consumes nitrogen in the porous skeleton, which has a negative effect on the cycle performance of the battery. Therefore, in some embodiments of the present application, the temperature for sintering the porous skeleton substrate loaded with a lithium-philic material precursor is preferably 400°C to 2500°C, and more preferably 800°C to 1000°C.

[0148] (4) Examples 1, 26 to 31

[0149] Examples 1 and 26 to 31 show the effect of the sintering time of the porous skeleton substrate loaded with the lithium-philic material precursor in an inert atmosphere on the technical effect of the present application.

[0150] As can be seen from Table 1, in Examples 1, 26 to 31, the sintering time of the porous skeleton substrate loaded with the lithium-philic material precursor solution in an inert atmosphere is 2h, 0.1h, 0.5h, 1h, 4h, 6h and 12h, respectively, and other materials and preparation process parameters are consistent. As can be seen from Table 2, with the increase of sintering time, the cycle performance of the lithium secondary battery shows a trend of first rising and then falling.

[0151] When the sintering time is too short (such as Example 26), the porous skeleton of the lithium buffer layer does not achieve optimal conductivity, which is not conducive to the migration and release of lithium metal from the buffer layer, resulting in limited improvement in the cycle performance of the lithium secondary battery.

[0152] As the sintering time increases, the conductivity of the lithium buffer layer is gradually improved. The lithium buffer layer's inhibition and induction of deposition of lithium dendrites of the metal lithium negative electrode gradually become obvious, and the improvement of the cycle performance of the lithium secondary battery also becomes significant. In Example 1, the porous skeleton substrate loaded with a lithium-philic material precursor solution is sintered in an inert atmosphere for 2 hours, which significantly improves the cycle performance of the lithium secondary battery.

[0153] However, if the sintering time is too long, it will not only waste energy, but also consume nitrogen in the porous skeleton, which will have a negative effect on the cycle performance of the battery. Therefore, in some embodiments of the present application, the sintering time of the porous skeleton substrate loaded with the lithium-philic material precursor is preferably 0.5 hours to 6 hours, more preferably 1 hour to 2 hours.

[0154] (5) Examples 1, 32 to 38

[0155] Examples 1 and 32 to 38 show the influence of the thickness of the porous skeleton substrate on the technical effect of the present application.

[0156] As can be seen from Table 1, the thickness of the porous skeleton substrate in Examples 1, 32 to 38 is 0.1 μm, 50 μm, 100 μm, 500 μm, 1000 μm, 10000 μm, and 50000 μm, respectively. Other materials and preparation process parameters are consistent. As can be seen from Table 2, with the increase in the thickness of the porous skeleton substrate, the cycle performance of the lithium secondary battery shows a trend of first rising and then falling.

[0157] When the thickness of the porous skeleton substrate is relatively thin (such as Example 32), the strength of the porous skeleton substrate is also relatively low. Therefore, using this porous skeleton substrate to prepare a lithium buffer layer will be detrimental to the long cycle of the battery, resulting in the lithium secondary battery's cycle performance improvement effect not being optimal.

[0158] As the thickness of the porous skeleton substrate increases, its strength is also improved, which is beneficial to the long cycle of the battery, and the cycle performance of the lithium secondary battery is further improved. However, the thicker the porous skeleton substrate is, the better it is. When the thickness of the porous skeleton substrate is too large, the lithium buffer layer prepared by using the porous skeleton substrate is added to the metal lithium negative electrode and assembled into a battery. Due to the excessive thickness of the lithium buffer layer, the liquid consumption phenomenon caused is serious, and its effect on improving the cycle performance of the lithium secondary battery is far less than that of Example 1.

[0159] Therefore, in some embodiments of the present application, the thickness of the porous skeleton is 1 μm to 10000 μm, preferably 50 μm to 1000 μm.

[0160] (II) The influence of the optional sulfidation, phosphating or nitriding treatment on the technical effect of the present application

[0161] Embodiments 39 to 41

[0162] The only difference from Example 1 is that the lithium buffer layer obtained after sintering is mixed with sulfur powder, sulfurization sintering is performed in an inert gas environment, and the internal sulfurization environment is ensured to be closed.

[0163] Embodiments 42 to 44

[0164] The only difference from Example 1 is that the lithium buffer layer obtained after sintering is mixed with phosphorus powder, phosphating sintering is performed in an inert gas environment, and the phosphating internal environment is ensured to be sealed.

[0165] Embodiments 45 to 47

[0166] The only difference from Example 1 is that the lithium buffer layer obtained after the sintering treatment is nitrided and sintered in a N2 or NH3 atmosphere.

[0167] The process parameters of the sulfurization treatment, phosphation treatment or nitridation treatment and the cycle performance of the lithium secondary battery in Examples 39 to 47 are shown in Table 3.

[0168] Table 3

[0169]

[0170] As can be seen from Table 3, through the optional sulfurization, phosphating and nitriding steps, the lithium-philic material in the porous skeleton is further transformed from metal oxide or non-metal oxide into metal sulfide, non-metal sulfide, metal phosphide, non-metal phosphide, metal nitride or non-metal nitride, which can also achieve the technical effect of guiding the uniform deposition of lithium metal in the lithium buffer layer, inhibiting the growth of lithium dendrites and improving the cycle life of lithium secondary batteries.

[0171] (III) Effect of the angle difference of molten lithium contact angle on the technical effect of the present application

[0172] Still using Examples 1 to 5, 14 to 19 and Comparative Example 3, the contact angles of molten lithium on the outer surface and inner surface of the lithium buffer layer were detected respectively, and then the angle difference between the two molten lithium contact angles was calculated to show the influence of the angle difference Δθ between the molten lithium contact angle on the outer surface of the lithium buffer layer and the molten lithium contact angle on the inner surface of the lithium buffer layer on the technical effect of the present application.

[0173] The numbers of the selected embodiments, the solutes in the lithium-philic material precursor solution, the time the porous skeleton substrate is immersed in the lithium-philic material precursor solution, the angle difference of the molten lithium contact angles on the upper and lower surfaces of the lithium buffer layer, and the battery cycle performance data are shown in Table 4.

[0174] Table 4

[0175]

[0176] Table 4 shows the contact angle of molten lithium on the outer surface of the lithium buffer layer, the contact angle of molten lithium on the inner surface of the lithium buffer layer, and the difference between the contact angles of molten lithium on the two surfaces, and their influence on the technical effect of the present application.

[0177] The contact angle of molten lithium on the inner surface of the lithium buffer layer is preferably 0° to 90°, at which point the inner surface of the lithium buffer layer has good lithium affinity; the contact angle of molten lithium on the outer surface of the lithium buffer layer is preferably 90° to 180°, at which point the outer surface of the lithium buffer layer has weak lithium affinity or is lithium-phobic, so that the lithium buffer layer can induce lithium metal to spontaneously deposit from the lithium-phobic side of the lithium buffer layer to the lithium-philic side, and finally deposit evenly inside the lithium buffer layer.

[0178] In addition, the angle difference between the contact angle of molten lithium on the outer surface of the lithium buffer layer and the contact angle of molten lithium on the inner surface of the lithium buffer layer is 10° to 180°, preferably 45° to 135°. When the angle difference between the contact angles of molten lithium on the outer surface and the inner surface of the lithium buffer layer is below 10°, the rate of change of the lithium affinity gradient between the inner and outer surfaces is too small, and the driving force for inducing the deposition of lithium metal from the lithium-phobic side to the lithium-philic side is insufficient. As a preferred solution, the angle difference between the contact angles of molten lithium on the outer surface and the inner surface of the lithium buffer layer is 45 to 135°, and a relatively obvious lithium affinity gradient change is presented between the inner and outer surfaces, which can effectively drive and induce the deposition of lithium metal from the lithium-phobic side to the lithium-philic side, and improve the deposition utilization rate of the internal space of the porous skeleton of the lithium buffer layer, effectively inhibit the growth of lithium dendrites, and effectively improve the cycle performance of lithium secondary batteries.

[0179] It can be seen from Table 4 that in Examples 14 and 15, the contact angle of molten lithium on the inner surface of the lithium buffer layer exceeds 90°, and the lithium affinity of the inner surface of the lithium buffer layer is relatively weak; in Example 19, the contact angle of molten lithium on the outer surface of the lithium buffer layer is less than 90°, and the lithium affinity of the outer surface of the lithium buffer layer is relatively high. Therefore, the cycle performance of Examples 14, 15 and 19 is inferior to that of other examples. At the same time, in Examples 14 and 19, the difference in the contact angles of molten lithium on the two surfaces is too small, and no obvious gradient change in lithium affinity is formed. Therefore, the cycle performance of Examples 14 and 19 is the least ideal among the examples in Table 2.

[0180] Those skilled in the art will appreciate that the various limitations or preferred ranges for component selection, component content, and material physicochemical performance parameters in the electrochemically active materials in the different embodiments of the present application mentioned above can be combined arbitrarily, and the various embodiments obtained by combining them are still within the scope of the present application and are deemed to be part of the disclosure of this specification.

[0181] According to the disclosure and teaching of the above description, those skilled in the art may also make changes and modifications to the above implementation. Therefore, the present application is not limited to the specific implementation disclosed and described above, and some modifications and changes to the present application should also fall within the scope of protection of the claims of the present application. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present application.

Claims

1. A composite metal lithium negative electrode, comprising metal lithium and a lithium buffer layer located on at least one surface of the metal lithium, characterized in that: The lithium buffer layer comprises a porous skeleton and a lithium-philic material, wherein the porous skeleton is a conductive porous skeleton, and the lithium-philic material is selected from one or more of the following substances having lithium-philicity: metal oxides, non-metal oxides, metal sulfides, non-metal sulfides, metal phosphides, non-metal phosphides, metal nitrides or non-metal nitrides; The lithium-philic material is distributed in the porous skeleton, and in the direction in which the lithium buffer layer is away from the metallic lithium, the distribution density of the lithium-philic material in the porous skeleton decreases in a continuous gradient; The lithium buffer layer has an inner surface close to the metal lithium and an outer surface away from the metal lithium. The contact angle of molten lithium on the inner surface of the lithium buffer layer is 0° to 90°, and the contact angle of molten lithium on the outer surface of the lithium buffer layer is 90° to 180°.

2. The composite metal lithium negative electrode according to claim 1, characterized in that In the direction in which the lithium buffer layer is away from the metal lithium, the contact angle of molten lithium in the cross section of the lithium buffer layer increases in a continuous gradient.

3. The composite metal lithium negative electrode according to claim 1 or 2, characterized in that: The angle difference Δθ between the contact angle of molten lithium on the outer surface of the lithium buffer layer and the contact angle of molten lithium on the inner surface of the lithium buffer layer is 10° to 180°.

4. The composite metal lithium negative electrode according to claim 3, characterized in that The angle difference Δθ between the contact angle of molten lithium on the outer surface of the lithium buffer layer and the contact angle of molten lithium on the inner surface of the lithium buffer layer is 45° to 135°.

5. The composite metal lithium negative electrode according to claim 1 or 2, characterized in that: The lithium-philic material is selected from one or more of zinc oxide, zinc sulfide, zinc phosphide, zinc nitride, aluminum oxide, aluminum nitride, magnesium oxide, magnesium sulfide, magnesium nitride, copper phosphide, copper nitride, silver oxide, silver sulfide, and boron nitride.

6. The composite metal lithium negative electrode according to claim 5, characterized in that The lithium-philic material is selected from one or more of zinc oxide and silver oxide.

7. The composite metal lithium negative electrode according to claim 1 or 2, characterized in that: The porous skeleton satisfies at least one of the following conditions (1) to (3): (1) The thickness of the porous skeleton is 1 μm to 10000 μm; (2) The porosity of the porous skeleton is 30% to 95%; (3) The pore size of the porous skeleton is 0.01 μm to 10 μm.

8. The composite metal lithium negative electrode according to claim 7, characterized in that: The thickness of the porous skeleton is 50 μm to 1000 μm.

9. A method for preparing a composite metal lithium negative electrode according to any one of claims 1 to 8, characterized in that: The steps include: dissolving a precursor of a lithium-philic material in a solvent to obtain a lithium-philic material precursor solution; Soaking one surface of the porous skeleton substrate in the lithium-philic material precursor solution, taking it out and drying it, to obtain a porous skeleton substrate loaded with the lithium-philic material precursor; The porous skeleton substrate loaded with the lithium-philic material precursor is subjected to sintering treatment, and optionally subjected to sulfurization treatment, phosphation treatment or nitridation treatment to obtain a lithium buffer layer; The lithium buffer layer is pressed onto at least one surface of the metallic lithium, and the surface of the porous skeleton substrate immersed in the lithium-philic material precursor solution is bonded to the metallic lithium to obtain a composite metallic lithium negative electrode.

10. The method for preparing a composite metal lithium negative electrode according to claim 9, characterized in that: The precursor of the lithium-philic material is selected from organic salts or inorganic salts containing zinc, aluminum, magnesium, copper, silver or boron. The organic salt is selected from bis(fluorosulfonyl)imide salt and / or bis(trifluoromethylsulfonyl)imide salt; the inorganic salt is selected from one or more of acetate, nitrate, sulfate, thiosulfate or aluminate.

11. The method for preparing a composite metal lithium negative electrode according to claim 9, characterized in that: The solvent is selected from one or more of water, ethanol, DMF or NMP.

12. The method for preparing a composite metal lithium negative electrode according to claim 9, characterized in that: The porous skeleton substrate satisfies at least one of the following conditions (1) to (3): (1) The thickness of the porous skeleton substrate is 1 μm to 10000 μm; (2) The porosity of the porous skeleton substrate is 30% to 95%; (3) The pore size of the porous skeleton substrate is 0.01 μm to 10 μm.

13. The method for preparing a composite metal lithium negative electrode according to claim 12, characterized in that: The thickness of the porous skeleton is 50 μm to 1000 μm.

14. The method for preparing a composite metal lithium negative electrode according to claim 9, characterized in that: The porous skeleton substrate is selected from one or more of melamine foam, polyurethane, polyethylene, polystyrene, polyvinyl chloride, polypropylene, polyacetylene, polythiophene, polypyrrole, polyaniline, pure carbon, carbon cloth or carbon paper.

15. The method for preparing a composite metal lithium negative electrode according to claim 9, characterized in that: The time for immersing one surface of the porous skeleton substrate in the lithium-philic material precursor solution is 2 minutes to 360 minutes.

16. The method for preparing a composite metal lithium negative electrode according to claim 15, characterized in that: The time for immersing one surface of the porous skeleton substrate in the lithium-philic material precursor solution is 30 minutes to 60 minutes.

17. The method for preparing a composite metal lithium negative electrode according to claim 9, characterized in that: The sintering process is carried out in an inert gas environment; the sintering time is 0.5 hours to 6 hours.

18. The method for preparing a composite metal lithium negative electrode according to claim 17, characterized in that: The sintering time is 1 to 2 hours.

19. The method for preparing a composite metal lithium negative electrode according to claim 9, characterized in that: The sintering temperature is 400℃~2500℃.

20. The method for preparing a composite metal lithium negative electrode according to claim 19, characterized in that: The sintering temperature is 800°C to 1000°C.

21. The method for preparing a composite metal lithium negative electrode according to claim 9, characterized in that: The sulfurization treatment comprises: mixing the lithium buffer layer obtained after the sintering treatment with sulfur powder, and performing sulfurization sintering in an inert gas environment; The phosphating treatment comprises: mixing the lithium buffer layer obtained after the sintering treatment with phosphorus powder, and performing phosphating sintering in an inert gas environment; The nitridation treatment comprises: nitridation sintering the lithium buffer layer obtained after the sintering treatment in a N2 or NH3 atmosphere.

22. The method for preparing a composite metal lithium negative electrode according to claim 21, characterized in that: The sulfurization sintering time is 0.5 hours to 6 hours, and the sulfurization sintering temperature is 400° C. to 1000° C.; The phosphating sintering time is 0.5 hours to 6 hours, and the phosphating sintering temperature is 400° C. to 1000° C.; The nitriding sintering time is 0.5 hours to 6 hours, and the nitriding sintering temperature is 400° C. to 1000° C.

23. A lithium secondary battery, characterized in that: It comprises the composite metal lithium negative electrode according to any one of claims 1 to 8.

24. A device, characterized in that: The lithium secondary battery according to claim 23 is included, and the lithium secondary battery is used as a power source of the device or an energy storage unit of the device.

Citation Information

Patent Citations

  • Gas diffusion electrode and fuel cell comprising such a gas diffusion electrode

    CN109643808A

  • Composite metal lithium negative electrode with filler and preparation method thereof

    CN110931712A

  • Lithium metal secondary battery anode current collector and preparation method thereof

    CN110993954A